2018
DOI: 10.1021/acs.analchem.8b01017
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoliter Cell Culture Array with Tunable Chemical Gradients

Abstract: A multitude of cell screening assays for diagnostic and research applications rely on quantitative measurements of a sample in the presence of different reagent concentrations. Standard methods rely on microtiter plates of varying well density, which provide simple and standardized sample addressability. However, testing hundreds of chemical dilutions requires complex automation, and typical well volumes of microtiter plates are incompatible with the analysis of a small number of cells. Here, we present a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Second, the assay time can be reduced by tuning the bacteria and resazurin concentrations, similar to previous works. 18,20,21 Third, macrAST currently generates antibiograms from bacteria following clinical single-colony isolation. Appending a device that can filter and concentrate bacterial cells from patient samples [17][18][19] before marcAST may obviate clinical isolation and enable direct AST from samples with monomicrobial infections, such as the plurality of samples from uncomplicated UTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the assay time can be reduced by tuning the bacteria and resazurin concentrations, similar to previous works. 18,20,21 Third, macrAST currently generates antibiograms from bacteria following clinical single-colony isolation. Appending a device that can filter and concentrate bacterial cells from patient samples [17][18][19] before marcAST may obviate clinical isolation and enable direct AST from samples with monomicrobial infections, such as the plurality of samples from uncomplicated UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,21 Third, macrAST currently generates antibiograms from bacteria following clinical single-colony isolation. Appending a device that can filter and concentrate bacterial cells from patient samples [17][18][19] before marcAST may obviate clinical isolation and enable direct AST from samples with monomicrobial infections, such as the plurality of samples from uncomplicated UTIs. 22 Finally, colorimetric identification of bacteria [23][24][25] may be implemented within our microwell array device and be performed in tandem with marcAST.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently, a number of studies have been reported using newly developed microfluidic technologies to overcome the disadvantages of conventional AST methods. [26][27][28][29][30] Since most of the microfluidic AST platforms are microscale-systems, they not only reduce the excess cells and reagents required but also make it possible to analyze the morphology and number of single cells, which significantly improve the resolution. 23,31,32 In general, these platforms of single cell analysis test the efficacy of antibiotics based on phenotypic alteration of bacterial cells, rather than growth level.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, microfluidic systems for single cell susceptibility testing and diagnostic applications have been developed recently. [25][26][27] Many of these new techniques rely on costly equipment, have a limited microorganism spectrum or do not yet effectively accelerate the determination of MIC values.…”
Section: Introductionmentioning
confidence: 99%